MEDIAÇÃO FAMILIAR EM PROCESSO: FORMAÇÃO DE JOVENS ESTUDANTES DO ENSINO SUPERIOR - QUEIROZ, Edna Mendonça Oliveira de (2008)
The main principles guiding this research is that of the Educational Culture and Processes. The objective of this thesis is to learn in which way the family, as a medium of socializing, continues to operate in the development of youth in actuality. An accentuated process of change that is currently taking place in traditional socializing structures, moreover, within the family and the school, due to the transformations taking place in today s society. Some specialists such as Dubet, Melucci and Singly, among others, theorize that in particular, the family was removed from its condition as a fundamental locus of the sociability of children and adolescents. Investigating students that were successful in their entrance exams in two of the most sought after programs at the Federal University of Goiás, Medicine and Law, verifying how the family was present within the process that culminated in this acceptance to the University for the student, particularly in the fewer number of cases of students who graduated from public high schools. This analysis consists of proceedings from a socioeconomic-cultural questionnaire acquired from the Admissions Centre of the Federal University of Goiás completed by the successful candidates and those who passed the entrance exams from 2005 to 2007 in the programs of Medicine and Law, as well as semi-structured interviews with the youth that were enrolled in the same semester, within these programs. In accordance with the referenced Adorno e Horkheimer, regarding the individual relations and those found within society, in addition to Freud s theory which entails the mechanisms of the identification that permit the analysis of the family as a social space as a determinant in which the psyche of the individual develops, this research paper will reveal the internalizing efficient familiar processes that will provide one with the realization of the tension that constitutes the internal relations when confronted with social reality, the internalized web through emotional support that, many times, does not allow itself to be recognized immediately. The conducted empirical study permits one to affirm that the families of the interviewed young prevail as referred in the constitution of youth, orientating them, directly or indirectly in their actions. The family, therefore, predominates with great vigor at the forefront of the other social spheres that encircle, contemporarily speaking, these youth.